PENGUATAN SIKAP TOLERANSI BERAGAMA MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DI SMP NEGERI 6 BANJARMASIN - Norasiah; Mariatul Kiptiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Religious tolerance is a very valuable value in diverse Indonesian society, especially in the school environment, which is a place of interaction between students with various religious backgrounds. This study aims to explain: (1) the attitude of mutual respect among students in Pancasila Education learning, (2) the role of the Pancasila Education learning process in strengthening attitudes of mutual respect, and (3) factors that influence success in strengthening attitudes of religious tolerance. The research method used is qualitative with observation, interview, and documentation techniques. The research findings show that students demonstrate attitudes of mutual respect through active participation, acceptance of different opinions, and avoidance of discrimination. The learning process plays a role through the use of discussion methods, role models from teachers, and connecting material with the context of diversity. Supporting factors include student awareness, examples given by teachers, school culture, and the social environment. It can be concluded that Pancasila Education has a significant role in strengthening attitudes of religious tolerance, especially in attitudes of respect for others.